Poisoning in Children and adolescents assisted during the COVID-19 pandemic at the Toxicological Information and Assistance Center in Federal District, Brazil (CIATOX -DF): Descriptive, Cross-sectional, and Analytical study with 1.037 patients (Research, Society and Development, 2021)
Exogenous poisonings are one of the principal accidents involving children and adolescents. The social isolation promoted by the COVID-19 pandemic raises concerns about the possibility of an increase in poisoning among children since most cases of poisoning occur in home environments. Therefore, the present study evaluated exogenous poisonings in children under ten years of age and adolescents aged 11 to 20 years old through data recorded at the Toxicological Information and Assistance Center in the Federal District (CIATOX-DF) from January to September 2020. The results showed a change in the number of notifications, with 1.037 poisonings registered in patients under 20 years of age. Registrations of poisoning by venomous animals, medications, and household cleaning products in children tend to be higher in months of vacation. This study demonstrated poisoning notifications by non-venomous animals in March and April and household cleaning products as the second leading cause of exogenous poisoning, demonstrating a clear temporal association among social isolation, increased use of household cleaning products, and exposure to these products. The multivariate analysis methodology managed to show the significant characteristics of the studied sample, contributing to creating local actions that aim to reduce the number of preventable cases of poisonings.